Here's the question you clicked on:
rubyhunter
x2-6x-6=0
we literally just told you how to solve these problems in the last one. For \(f(x)=ax^2+bx+c=0\) \[x = \frac{-b\pm\sqrt{b^2 - 4ac}}{2a}\]Is there something you don't understand? If so just ask! We're not here to do other peoples homework for them!
ummm ur being rude the other one was easy this one has me confused, and just givin me a formula where i can miss up isnt helpin me -_-
what answer did you get when you tried plugging into the formula?
\[\left( x-3 \right)^{2}-3^{2}-6=0\] \[\left( x-3 \right)^{2}-15=0\] \[\left( x-3 \right)^{2}=15\] \[\left( x-3 \right)=\pm \sqrt{15}\] \[x =\pm \sqrt{15}+3\] \[x =\sqrt{15}+3\] or \[x =3-\sqrt{15}\]